New Urea Derivatives Are Effective Anti-senescence Compounds Acting Most Likely via a Cytokinin-Independent Mechanism - Nisler, Jaroslav; Zatloukal, Marek; Sobotka, Roman; Pilný, Jan; Zdvihalová, Barbora; Novák, Ondrej; Strnad, Miroslav; Spíchal, Lukáš (Frontiers in Plant Science, 2018)
Stress-induced senescence is a global agro-economic problem. Cytokinins are considered to be key plant anti-senescence hormones, but despite this practical function their use in agriculture is limited because cytokinins also inhibit root growth and development. We explored new cytokinin analogs by synthesizing a series of 1,2,3-thiadiazol-5-yl urea derivatives. The most potent compound, 1-(2-methoxy-ethyl)-3-1,2,3-thiadiazol-5-yl urea (ASES - Anti-Senescence Substance), strongly inhibited dark-induced senescence in leaves of wheat (Triticum aestivum L.) and Arabidopsis thaliana. The inhibitory effect of ASES on wheat leaf senescence was, to the best of our knowledge, the strongest of any known natural or synthetic compound. In vivo, ASES also improved the salt tolerance of young wheat plants. Interestingly, ASES did not affect root development of wheat and Arabidopsis, and molecular and classical cytokinin bioassays demonstrated that ASES exhibits very low cytokinin activity. A proteomic analysis of the ASES-treated leaves further revealed that the senescence-induced degradation of photosystem II had been very effectively blocked. Taken together, our results including data from cytokinin content analysis demonstrate that ASES delays leaf senescence by mechanism(s) different from those of cytokinins and, more effectively. No such substance has yet been described in the literature, which makes ASES an interesting tool for research of photosynthesis regulation. Its simple synthesis and high efficiency predetermine ASES to become also a potent plant stress protectant in biotechnology and agricultural industries.